The role of transformational leadership in navigating digital servitization - Florian Tagscherer; Claus-Christian Carbon (Sustainable Technology and Entrepreneurship)
Digital servitization converges two current innovation activities in industrial companies: shifting from product-oriented to service-oriented business models and integrating digital technologies in market offerings. Adding digitalized services offers significant growth and diversification opportunities, but companies have struggled to reap its potential. Establishing digital servitization business models is underpinned by complexity, making it difficult for companies to manage. Digital servitization is a relatively new research stream, especially needing more guidance on how companies should be led to succeed in its implementation. We addressed this research gap and conducted thirty semi-structured interviews with leaders in digital servitization holding ranks ranging from first-level Managers to Vice Presidents and Executives with more than 20 years of leadership experience active in industries such as machinery, electrical equipment, or IT services. We identified transformational leadership as vital to building digital servitization business models and navigating their inherent complexity and change management requirements. Our findings include three focus areas as recommendations for leadership: giving direction, being employee-oriented, and creating an innovative and collaborative environment. Furthermore, transactional leadership aspects should be considered for specific use cases to maintain the business model, for example, improving after a certain amount of time or managing crisis mode.